2017
DOI: 10.5897/jene2017.0622
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the abundance of Anubis baboons (Papio anubis) and conflict with humans in Trigni Forest of Gida Ayana District, Western Ethiopia

Abstract: Among baboon species, Papio anubis is the most broadly distributed species, ranging through most of central sub-Saharan of Africa. Papio anubis live in troops but the size varies in different area. There are three troops of P. anubis in Trigni forest with 149 to 180 members in each troop. The objective was to assess the abundance of Anubis baboon (AB) and their conflict with humans with respect to the livelihood of local farmers in Trigni forest of Gida Ayana district, Western Ethiopia. Counting was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The baboons feed on crops like maise, the red‐river hogs feed on the roots of some crops, and the duikers eat leaves, fruits and seeds of crops. Baboons spend time on farms raiding crops because of readily available food (Fehlmann et al, 2017; Mosissa et al, 2017; Pebsworth et al, 2012). Similarly, Bamford et al (2014) reported that different animals were attracted to farms bordering the Selous Game Reserve in Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…The baboons feed on crops like maise, the red‐river hogs feed on the roots of some crops, and the duikers eat leaves, fruits and seeds of crops. Baboons spend time on farms raiding crops because of readily available food (Fehlmann et al, 2017; Mosissa et al, 2017; Pebsworth et al, 2012). Similarly, Bamford et al (2014) reported that different animals were attracted to farms bordering the Selous Game Reserve in Tanzania.…”
Section: Discussionmentioning
confidence: 99%